2021
DOI: 10.1088/1755-1315/723/5/052005
|View full text |Cite
|
Sign up to set email alerts
|

Impact factory assessment on the air on the Pekhorka river basin

Abstract: The background ecological situation on Pekhorka river of the Balashikha district is determined by its location in the eastern part of the Moscow agglomeration. Most of the neighboring industrial centers are located to the west of it, from the side of the prevailing winds. Enterprises harm the air state during construction works. The vast majority of the enterprises are concentrated on the territory of Balashikha. The article discusses an example of calculating air pollution from the enterprise influencing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
0
0
3
Order By: Relevance
“…Finally, it is observed that the 'Factory-Industry' variable harmed bare/sparse vegetation coverage, suggesting an increase in NO2 concentrations at shorter distances from factories or industries (Table 2). Factories and industries are known to be significant sources of gas emissions, including NO2, as a result of manufacturing processes and fuel combustion [56].…”
Section: No2mentioning
confidence: 99%
“…Finally, it is observed that the 'Factory-Industry' variable harmed bare/sparse vegetation coverage, suggesting an increase in NO2 concentrations at shorter distances from factories or industries (Table 2). Factories and industries are known to be significant sources of gas emissions, including NO2, as a result of manufacturing processes and fuel combustion [56].…”
Section: No2mentioning
confidence: 99%
“…Все это негативным образом влияет на качество атмосферы и окружающей природной среды, ухудшая состояние здоровья населения. Вредное воздействие промышленности и энергопотребления на окружающую среду и здоровье населения имеет не только местный и региональный, но и глобальный характер [1][2][3][4].…”
Section: Abstract: Road Transport Pollutants Mass and Concentration O...unclassified
“…В связи с этим, для контроля уровня качества атмосферного воздуха и состояния окружающей природной среды нужно осуществлять экологический мониторинг (мониторинг окружающей природной среды), который представляет собой комплекс мероприятий, направленных на исследование: качества окружающей среды, в том числе ее компонентов; происходящих в них процессов и явлений; изменений состояния окружающей среды в целом [3,4].…”
Section: Abstract: Road Transport Pollutants Mass and Concentration O...unclassified
See 1 more Smart Citation